Risk factors and survival of patients infected with carbapenem-resistant Klebsiella pneumoniae in a KPC endemic setting: a case-control and cohort study (2019)
ABSTRACT : Background: Many gaps in the burden of resistant pathogens exist in endemic areas of low- and middle-income economies, especially those endemic for carbapenem resistance. The aim of this study is to evaluate risk factors for carbapenem-resistance, to estimate the association between carbapenem-resistance and all-cause 30-day mortality and to examine whether mortality is mediated by inappropriate therapy. Methods: A case-control and a cohort study were conducted in one tertiary-care hospital in Medellín, Colombia from 2014 to 2015. Phenotypic and genotypic characterization of isolates was performed. In the case-control study, cases were defined as patients infected with carbapenem-resistant K. pneumoniae (CRKP) and controls as patients infected with carbapenem-susceptible K. pneumoniae (CSKP). A risk factor analysis was conducted using logistic regression models. In the cohort study, the exposed group was defined as patients infected with CRKP and the non-exposed group as patients infected with CSKP. A survival analysis using an accelerated failure time model with a lognormal distribution was performed to estimate the association between carbapenem resistance and all-cause 30-day-mortality and to examine whether mortality is mediated by inappropriate therapy. Results: A total of 338 patients were enrolled; 49 were infected with CRKP and 289 with CSKP. Among CRKP isolates CG258 (n = 29), ST25 (n = 5) and ST307 (n = 4) were detected. Of importance, every day of meropenem (OR 1.18, 95%CI 1.10–1.28) and cefepime (OR 1.22, 95%CI 1.03–1.49) use increase the risk of carbapenem resistance. Additional risk factors were previous use of ciprofloxacin (OR 2.37, 95%CI 1.00–5.35) and urinary catheter (OR 2.60, 95%CI 1.25–5.37). Furthermore, a significant lower survival time was estimated for patients infected with CRKP compared to CSKP (Relative Times 0.44, 95%CI 0.24–0.82). The strength of association was reduced when appropriate therapy was included in the model (RT = 0.81 95%CI 0.48–1.37). Conclusion: Short antibiotic courses had the potential to reduce the selection and transmission of CRKP. A high burden in mortality occurred in patients infected with CRKP in a KPC endemic setting and CRKP leads to increased mortality via inappropriate antibiotic treatment. Furthermore, dissemination of recognized hypervirulent clones could add to the list of challenges for antibiotic resistance control.